Unveiling TiNb2O7 as an insertion anode for lithium ion capacitors with high energy and power density - Ramakrishna, Seeram (2014)
This is the first report of the utilization of TiNb2O7 as an insertion-type anode in a lithium-ion hybrid electrochemical capacitor (Li-HEC) along with an activated carbon (AC) counter electrode derived from a coconut shell. A simple and scalable electrospinning technique is adopted to prepare one-dimensional TiNb2O7 nanofibers that can be characterized by XRD with Rietveld refinement, SEM, and TEM. The lithium insertion properties of such electrospun TiNb2O7 are evaluated in the half-cell configuration (Li/TiNb2O7) and it is found that the reversible intercalation of lithium (≈3.45 mol) is feasible with good capacity retention characteristics. The Li-HEC is constructed with an optimized mass loading based on the electrochemical performance of both the TiNb2O7 anode and AC counter electrode in nonaqueous media. The Li-HEC delivers very high energy and power densities of approximately 43 Wh kg−1 and 3 kW kg−1, respectively. Furthermore, the AC/TiNb2O7 Li-HEC delivers a good cyclability of 3000 cycles with about 84 % of the initial value.